QUO ANNIMO NATIONAL CHARACTER (REVITALIZING IAIN'S ROLE IN REALIZING PROFESSIONAL AND MORAL HRM) - Lukman Hakim (CV Naskah Aceh, 2022)
Indonesia is a country rich in natural resources, but its prosperous natural potential has never been able to lead its people to progress, supposedly becoming a civil society. The reality today is that Indonesia cannot even rise from the status quo which remains with the status of a developing country. It is not the fault of the earth on which we stand, but rather that the managers of the nation and its society are increasingly losing their identity as religious and moral human beings. Our increasingly distorted civilization has caused the erosion of the nation's noble character values. If we agree to improve the fate of the nation, of course we must start developing the mentality of the nation's children with character education. IAIN as an educational institution represents a